Organic pollutants : - Walker, C. H (Taylor & Francis, 2009)
The book takes a bottom up approach, describing the mechanisms by which pollutants have harmful effects on living organisms and how these effects are translated into adverse changes at the population level. This mechanistic approach supplies the basis for development of new mechanistic biomarker assays, which in turn provide measures of toxic effect and not merely of exposure, and subsequently provide evidence of causality between pollutant levels and ecological changes